EFFECT OF MICROWAVE HEATING ON QUALITY AND FATTY ACIDS COMPOSITION OF VEGETABLE OILS - POP, Flavia (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The research was conducted in order to evaluate the microwave effect on fatty acids profile and quality parameters of safflower and rapeseed oils. To simulate conventional times used in microwave domestic cooking, different exposure times were tested: 1, 3, and 5, respectively. After 5 minutes of microwave exposure, the peroxide index showed a significant increase for both types of oil (P≤0.05). Rapeseed fatty acids profile was rich in olei (C18:1), vaccenic (C18:1i), linoleic (C18:2), palmitic (C16:0) and linolenic (C18:2) fatty acids, followed by miristic (C17:0) and stearic (C18:0) acids. Microwave heating inflicted changes in fatty acids profile of both oils, the most affected fraction was the polyunsaturated fatty acids, directly related with their higher number of double bonds, with higher susceptibility to oxidation. Microwave heating exerted more aggressive effects on safflower oil, and rapeseed oil can be exposed for 5 minutes without negative effects.